2013
DOI: 10.1155/2013/503419
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Polyps in Women Affected by Levothyroxine-Treated Hypothyroidism—Histological Features, Immunohistochemical Findings, and Possible Explanation of Etiopathogenic Mechanism: A Pilot Study

Abstract: The aim of the study was to investigate the possible overexpression of estrogen (ERs) and progesterone (PRs) receptors both in EPs glandular and stromal cells in postmenopausal women with levothyroxine-treated hypothyroidism in comparison to EPs detected in women with physiological thyroid hormone levels. During the study period (January-February 2013) 22 patients were eligible (12 treated, 10 controls). The two groups were homogenous for general, EPs sonographic and hysteroscopic features. None of the cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
0
11
1
1
Order By: Relevance
“…From this ex vivo study on thyroid transcripts in patients with endometriosis, an increase in TSH (hypothyroidism) or in thyroid hormone T4 (hyperthyroidism or T4 intake) could be hypothesized as a participating factor for endometriosis aggravation. Interestingly, it has already been shown that thyroid hormone, especially T4, correlated with polyp aggravation without mechanistical evidence (27). Cross-talk between thyroid hormones and estrogens has been suggested by the direct stimulation of estrogen receptors on endometrial cells by thyroid hormones, leading to cell proliferation (28).…”
Section: Discussionmentioning
confidence: 99%
“…From this ex vivo study on thyroid transcripts in patients with endometriosis, an increase in TSH (hypothyroidism) or in thyroid hormone T4 (hyperthyroidism or T4 intake) could be hypothesized as a participating factor for endometriosis aggravation. Interestingly, it has already been shown that thyroid hormone, especially T4, correlated with polyp aggravation without mechanistical evidence (27). Cross-talk between thyroid hormones and estrogens has been suggested by the direct stimulation of estrogen receptors on endometrial cells by thyroid hormones, leading to cell proliferation (28).…”
Section: Discussionmentioning
confidence: 99%
“…Because polyps contain functional endometrium, they can develop in conditions associated with increased or unopposed E 2 levels, as in the case of ovarian stimulation during IVF (10,15,20). Molecular mechanisms, including the overexpression of estrogen and progesterone receptors (25), endometrial aromatase (26,27), and mutations in the HMGIC and HMGI[Y] genes (28,29), also have been implicated in the development of endometrial polyps (20). Polyps may adversely affect fertility by mechanically interfering with sperm transportation or as space-occupying lesions impeding embryo implantation (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with concurrent primary malignancies, EC of non-endometrioid histological type, previous use of hormone replacement therapy or raloxifene, levothyroxine treatment (16,17), or a history of pelvic irradiation or intrauterine hysteroscopic surgery for metrorrhagia (<1 year prior to EEC diagnosis) (18) were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%